Bengali Short Stories and the Anti-Scriptural Movement/ বাংলা ছোটগল্প ও শাস্ত্রবিরোধী আন্দোলন (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
A certain art form of the short story was solidified in Bengali literature by the pen of Rabindranath Tagore in the last decade of the nineteenth century. The roots of that story-concept were also in the ideals of the modern short story that emerged in the first half of the nineteenth century. In the first half of the nineteenth century, a standard of structure and style for the short story was established in the writings of Washington Irving, Nathaniel Hawthorne, Edgar Allan Poe, and others. This influence continued in the second half of the nineteenth century in the writings of Maupassant and other European short story writers. Rabindranath was also a follower of that trend.             Overall, it can be said that this ideal was valid in Bengali short stories from the last decade of the nineteenth century to the first decade after independence. The social background has changed with the flow of time. Many new subjects have emerged as the basis of stories, and new types of characters have appeared in keeping with the times.             Stories published in magazines like ‘Kallol’ and ‘Kalikalam’ between 1923-30, which depict the cruel and difficult aspects of life. After 1930, the anti-fascist movement left an impact on Bengali short stories. The Second World War took place between 1939 and 1945. During this time, the Quit India Movement, the Partition of Bengal, and the form of capitalist exploitation emerged in Bengali short stories. Nevertheless, the original mold of the short story remained the same.            The social, political, and economic conditions of Bengal were extremely complex and turbulent during the 1950s, from 1950 to 1959. From the middle of this decade, some writers began to perceive life and the realities of life in a slightly different way. They tried to reflect reality in literature from a different perspective. A new trend in storytelling emerged.             The writers of this new trend, by defying the conventional structure of the short story, created a circle of light and darkness around the subtle layers of political and psychological nuances. Starting from the 1950s, stories were written in various new trends like ‘Desh’, ‘Porichoy’, ‘Notun Sahitya’, ‘Sahityapatra’ and others. A new style emerged in Bengali short stories, a new trend in storytelling.            In the 1960s, a few new writers started writing stories in a new way, rejecting the conventional story trend. A turning point occurred in Bengali short stories, and the new internal realism emerged. The writers of this magazine named their storytelling style ‘anti-scriptural’ stories. The writers of the 1950s had given a clear and artistic form to reality, but they did not completely abandon narration. They wrote diverse stories in their own way. However, the anti-scriptural writers completely rejected the narrative element in stories.            Some of these new storytellers included Ramananda Ray, Shekhar Basu, Kalyan Sen, Ashish Ghosh, Subrata Sengupta, Amal Chanda, Balaram Basak, Sunil Jana, and others.          A turning point occurred in Bengali short stories. Internal reality was expressed more than external reality. In these stories, the plot and characters did not develop following the logical path of everyday reality. The feelings and experiences of the human mind, gains and losses, and the discourse of light and darkness became the central themes of these stories. Sometimes they were mysterious, sometimes bizarre, and sometimes the storytelling technique was mechanical. A new approach emerged in the planning of the structure of these stories. These writers expressed the mental state of individuals and society as they wished, which was completely different from the conventional structure of short stories.
Keywords: Bengali literature; short stories; Rabindranath Tagore; magazine; Anti-Scriptural Movement; Anti-fascist movement; external reality; Internal reality; mysterious; bizarre